Analisis Pengaruh Resonansi Merek dan Kepercayaan Merek terhadap Loyalitas Merek Pengguna Produk Kecantikan Somethinc di Surakarta - Meylda Anan Maulidya; Sri Murwanti (Economic Reviews Journal, 2024)
The purpose of this research is to investigate how trust and brand resonance affect the brand loyalty of users of somethinc beauty products in Surakarta. The target audience of this research is people in the Surakarta area who use Somethinc beauty products. A total of 100 respondents who live in the Surakarta area and are more than 17 years old are the samples used. The result showed that the brand resonance variable had a positive and significant effect on the brand loyalty of Somethinc beauty products users in Surakarta. Brand trust variables have a significant effect on the brand loyalty of Somethinc beauty product users in Surakarta. Brand trust variable has a significant effect on brand loyalty of Somethinc beauty product users in Surakarta. The findings of f2 calculation show that brand resonance and brand loyalty are adequately correlated. Based on the calculation of R2 value, changes in brand loyalty variables can be explained by changes in brand resonance and brand trust variables.